2012
DOI: 10.3310/hta16390
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of enzyme and substrate replacement therapies: a longitudinal cohort study of people with lysosomal storage disorders.

Abstract: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 16, No. 39. See the HTA programme website for further project information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
147
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(159 citation statements)
references
References 0 publications
1
147
1
10
Order By: Relevance
“…O artigo, que analisou o custo-efetividade da TRE em MPS II (n = 58) e em outras doenças lisossômicas, não foi incluído na presente revisão por reunir dados retrospectivos além dos prospectivos. A única constatação estatisticamente significativa entre os pacientes com MPS II do trabalho foi a relação entre a duração da TRE e o crescimento em crianças 31 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O artigo, que analisou o custo-efetividade da TRE em MPS II (n = 58) e em outras doenças lisossômicas, não foi incluído na presente revisão por reunir dados retrospectivos além dos prospectivos. A única constatação estatisticamente significativa entre os pacientes com MPS II do trabalho foi a relação entre a duração da TRE e o crescimento em crianças 31 .…”
Section: Discussionunclassified
“…A alternativa existente à TRE seria o TCTH, porém esta terapia tem limitações importantes associadas à alta morbimortalidade, como desenvolvimento de doença do enxerto versus hospedeiro, rejeição do enxerto e infecções após o procedimento 31 . A principal vantagem dessa estratégia em relação à TRE seria o potencial efeito sobre a doença neurológica, haja vista que a IDS provavelmente não ultrapassa a barreira hematoencefálica; todavia, na literatura, são escassos os relatos prospectivos sobre TCTH na MPS II.…”
Section: Discussionunclassified
“…It is clear that such yearly gain is unrealistic, which makes it understandable, if one considers performing a cost-effectiveness or cost-utility analysis infeasible [34].…”
Section: Implications and Recommendations For Future Studiesmentioning
confidence: 99%
“…Recently, a health technology assessment in the UK showed that at least 3.6 discounted QALYs for an adult patient with Fabry disease are needed each year for ERT to be costeffective, considering a willingness-to-pay of £30 000 [34].…”
Section: Implications and Recommendations For Future Studiesmentioning
confidence: 99%
“…16 ERTs for six such disorders-Fabry disease, type I Gaucher disease, Pompe disease, and three types of mucupolysaccharidoses (MPS; MPS I, MPS II, and MPS VI)-have received regulatory approval in several jurisdictions. 18,19 However, there is considerable debate about providing patients with access to ERTs, particularly within publicly funded drug programs. 20 An important characteristic of lysosomal storage disorders is a high degree of heterogeneity among patients with the same specific disease.…”
Section: Outcomes: Defining Effectivenessmentioning
confidence: 99%